2020
DOI: 10.1109/access.2020.2995941
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Chinese Stock Price Index and Exchange Rates-An Evidence From the Belt and Road Initiative

Abstract: This paper selects the daily data of the exchange rates of Chinese Yuan (CNY) over the currencies of 14 countries along the Belt and Road, Shanghai composite index and Shenzhen composite index to study the influence of the Belt and Road Initiative on the linkages between exchange rates and Chinese stock index based on the flow-oriented model and the stock-oriented model. To reflect the fluctuations in daily data and reduce the central bank's interference with the exchange rate, two fuzzy techniques are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…When this occurs for a very long time, the local currency becomes cheaper to induce local demand for goods. is finally occasions appreciation of the local currency which drives the cost of export to enterprises to reflect a fall in stock returns (Yuan et al, 2020) as can be found in the long term between 2013 and 2016 for Zambia.…”
Section: Bi-wavelet Analysismentioning
confidence: 96%
“…When this occurs for a very long time, the local currency becomes cheaper to induce local demand for goods. is finally occasions appreciation of the local currency which drives the cost of export to enterprises to reflect a fall in stock returns (Yuan et al, 2020) as can be found in the long term between 2013 and 2016 for Zambia.…”
Section: Bi-wavelet Analysismentioning
confidence: 96%